Assessing future needs of IT education in Malaysia: a preliminary result - Ahlan, Abdul Rahman; Suhaimi, Mohd Adam; Hussin, Husnayati; Arshad, Yusri (WSEAS Press, 2008)
Malaysia is making a frantic effort to promote its shared services and outsourcing as a preferred hub in Asia. It is projected for multiple growths in demand for IT graduates to fulfill this IT outsourcing phenomenon. In this study, we sought in-depth insights and experiences from seven senior executive managements in service provider firms in Klang Valley on the skills and capabilities requirements of fresh IT graduates to fulfill the market needs of IT outsourcing in Malaysia. The research team found that technical, soft and problem-solving skills are the main concerns raised by the key informants. This is in line with the literature review and also the present higher education policy concerns by the Malaysia government. The second stage of the study is to survey across West Malaysia and finally a roundtable discussion with panel of experts from academia and industry will be conducted in order to reach to a conclusive and consensus agreements.